Improving Science Process Skill in Science Subject in Elementary School - Siagian, Novia G.; Wardani, Sri; Widiarti, Nuni; Yuwono, Agus (Universitas Negeri Padang, 2025)
Science process skills (SPS) are essential to be developed from the elementary level to foster students' critical and scientific thinking abilities. This study is a literature review of 20 national and international scientific articles published between 2020 and 2025. The method used is a qualitative and quantitative analysis to examine effective learning approaches for improving SPS. The findings indicate that discovery learning, ethno-STEM, simple experiments, and inquiry-based learning significantly enhance SPS. The study concludes that active and contextual learning strategies are crucial for developing SPS in elementary school students.